Effect of the sodium glucose co‐transporter 2 inhibitor canagliflozin on plasma volume in patients with type 2 diabetes mellitus. Issue 11 (8th July 2014) - Sha, S.; Polidori, D.; Heise, T.; Natarajan, J.; Farrell, K.; Wang, S.‐S.; Sica, D.; Rothenberg, P.; Plum‐Mörschel, L.
<x xml:space="preserve">Abstract</x> Aim To evaluate the effects of canagliflozin on plasma volume, urinary glucose excretion (UGE), fasting plasma glucose (FPG), glycated haemoglobin (HbA1c) and additional measures of fluid/electrolyte balance in patients with type 2 diabetes on background therapy with metformin and angiotensin‐converting enzyme inhibitors or angiotensin receptor blockers. Methods Patients (N = 36) were randomized (1 : 1) to receive canagliflozin 300 mg or placebo for 12 weeks. Pharmacodynamic parameters were assessed at baseline and at weeks 1 and 12. Results Increased 24‐h UGE was seen in the canagliflozin group compared with a reduction in the placebo group at both week 1 (91.8 vs. −2.4 g) and week 12 (82.6 vs. −0.4 g). Canagliflozin also reduced both FPG and HbA1c. Reductions in body weight and blood pressure were observed at weeks 1 and 12. Canagliflozin decreased plasma volume compared with an increase with placebo at week 1 (−5.4 vs. 4.3%; p = 0.02), but this was largely attenuated at week 12 (4.6 vs. 5.8%; p = 0.76). A modest numerical increase in urine volume was observed with canagliflozin at week 1 that was attenuated at week 12; other measures of volume status (i.e. blood urea nitrogen, serum creatinine and haematocrit) remained modestly increased with canagliflozin at week 12. Conclusion Canagliflozin provided sustained effects on UGE and FPG over 12 weeks and a transient reduction in plasma volume that was largely attenuated by week 12.